Application of Green Chemistry in the Context of Industrial Chemistry: Student Perspective and Importance for Continuing Study - Monica Lauren Sinuraya; Daffa Alaauddin Dzaki; Anisa Agustin; Hilda Nurhildayanti (Penerbit Hellow Pustaka, 2024)
Chemicals pose potential hazards to human health and the environment when used unwisely, carelessly, uncontrolled, incorrectly, and unsafely. Although Green Chemistry is strongly related to environmental issues, Green Chemistry-based learning also has a significant impact on students' learning achievement as well as skills in the learning process by providing a safe, interesting, and entertaining perspective of chemistry. This research uses the Focus Group Discussion (FGD) method to collect the necessary data on the concept of green chemistry in the context of industrial chemistry in schools. This research was conducted online through the Google Meet platform on November 10, 2023. In this study, we interviewed three respondents who are grade XI students at SMKN 7 Bandung majoring in industrial chemistry. The results of the Focus Group Discussions (FGDs) show that the respondents believe that the concept of Green Chemistry will have a high relevance in the context of the chemical industry, both in terms of practical applications and educational aspects. Green Chemistry is considered to have a positive and significant impact in the industrial context, both now and especially in the future. As the future generation in the industrial sector, the students showed great enthusiasm and interest in the application of Green Chemistry in various industrial processes.